High Temperature Deformation Behavior of 8090 Al-Li Alloy. (29th July 2013) - Jung, Woo Young; Ha, Tae Kwon
Abstract : High temperature deformation behavior, especially the superplasticity of an 8090 Al-Li alloy, was studied within the recent framework of the internal variable theory of structural superplasticity. In this study, a series of load relaxation tests were conducted at various temperatures ranging from 200°C to 530°C to obtain the flow curves of log ε ˙ versus log ε . The effect of grain size was also examined by varying the grain sizes through a proper thermomechanical treatment. The flow curves were found to be composite curves consisting of contributions from grain boundary sliding (GBS) and grain matrix deformation (GMD) at superplastic temperatures. The activation energy obtained for GMD was 124.9 kJ/mole in the temperature range from 470°C to 530°C, very similar to that for self-diffusion in pure Al.